CHEMICAL CHARACTERIZATION OF THE STEVIA REBAUDIANA - Bravo A., M. (2009)
Aqueous extractions were performed controlling the pH with CaCO3 and Ca(OH)2, using as clarifiers activated coal and activated clays in cold and warm solutions to obtain best results with cold bentonite, warm activated clay and warm activated coal. Analytical results were compared with a commercial sample of stevia.